2001
DOI: 10.1002/1099-0518(20010315)39:6<765::aid-pola1050>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Reverse atom transfer radical polymerization of methyl methacrylate with a new catalytic system, FeCl3/isophthalic acid

Abstract: A new catalytic system, FeCl3/isophthalic acid, was successfully used in the reverse atom transfer radical polymerization (RATRP) of methyl methacrylate (MMA) in the presence of a conventional radical initiator, 2,2′‐azo‐bis‐isobutyrontrile. Well‐defined poly(methyl methacrylate) (PMMA) was synthesized in an N,N‐dimethylformamide solvent at 90–120 °C. The polymerization was controlled up to a molecular weight of 50,000, and the polydispersity index was 1.4. Chain extension was performed to confirm the living n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…It has been reported that reverse ATRP of methyl methacrylate was successfully carried out with SmCl 3 /lactic acid catalyst system (38). Other organic acids, such as pyromellitic acid (39), isophthalic acid (40)(41)(42)(43), imiondiacetic acid (44,45), and succinic acid (46,47) have also been acted as a ligand in ATRP and reverse ATRP systems.…”
Section: Introductionsupporting
confidence: 90%
“…It has been reported that reverse ATRP of methyl methacrylate was successfully carried out with SmCl 3 /lactic acid catalyst system (38). Other organic acids, such as pyromellitic acid (39), isophthalic acid (40)(41)(42)(43), imiondiacetic acid (44,45), and succinic acid (46,47) have also been acted as a ligand in ATRP and reverse ATRP systems.…”
Section: Introductionsupporting
confidence: 90%
“…The control of macromolecular architecture has become an important topic of contemporary polymer science because well‐defined polymer microstructures promise new material properties. Nowadays, significant progress has been made in the field of living free‐radical polymerization, including nitroxide‐mediated stable free‐radical polymerization,1–4 atom transfer radical polymerization (ATRP),5–10 reverse ATRP,11–14 and reversible addition–fragmentation chain transfer 15–18. Among them, transition‐metal‐mediated ATRP has been extensively studied and successfully applied to the synthesis of well‐defined macromolecular architectures such as comb,19–21 star,22–25 and dendritic macromolecules 26–30.…”
Section: Introductionmentioning
confidence: 99%
“…A similar phenomenon has also been observed in refs. [14][15][16]. Some side reactions maybe occurred during the process of polymerization because NBS is a highly regioselective bromination reagent [9,10].…”
Section: Resultsmentioning
confidence: 99%